Dietary Supplement Use in the United States: Prevalence, Trends, Pros, and Cons. Issue 4 (July 2020) - Moore, Jeff; McClain, Amanda; Hong, Mee Young
Abstract : The history and trends in use of dietary supplements as documented in the National Health and Nutrition Examination Survey are summarized. The safety and efficacy of selected supplements are discussed. The current regulation of dietary supplements is not robust because legislation governing enforcement is weaker than it is for drugs.